Gold single-atoms confined at the CeOx-TiO2 interfaces with enhanced low-temperature activity toward CO oxidation. (22nd January 2023) - Kang, Eunji; Choi, Jungwoo; Choi, Hyuk; Yun, Jieun; Lee, Ju Hyeok; Yoo, Mi; Kim, Chunjoong; Lee, Hyuck Mo; Kim, Hyun You
Abstract: We use CeO x -TiO2 hetero-interfaces generated on the surface of CeO x -TiO2 hybrid oxide supporting powders to stabilize Au single-atoms (SAs) with excellent low-temperature activity toward CO oxidation. Based on intriguing density functional theory calculation results on the preferential formation of Au-SAs at the CeO x -TiO2 interfaces and the high activity of Au-SAs toward the Mars–van Krevelen type CO oxidation, we synthesized a Au/CeO x -TiO2 (ACT) catalyst with 0.05 wt.% of Au content. The Au-SAs stabilized at the CeO x -TiO2 interfaces by electronic coupling between Au and Ce showed improved low-temperature CO oxidation activity than the conventional Au/TiO2 control group catalyst. However, the light-off profile of ACT showed that the early activated Au-SAs are not vigorously participating in CO oxidation. The large portion of the positive effect on the overall catalytic activity from the low activation energy barrier of ACT was retarded by the negative impact from the decreasing active site density at high temperatures. We anticipate that the low-temperature activity and high-temperature stability of Au-SAs that stand against each other can be optimized by controlling the electronic coupling strength between Au-SAs and oxide clusters at the Au-oxide-TiO2 interfaces. Our results show that atomic-precision interface modulation could fine-tune the catalytic activity and stability of Au-SAs.